Acceptance of climate-oriented policy measures under the COVID-19 crisis: an empirical analysis for Germany. (26th November 2021) - Engler, Daniel; Groh, Elke D.; Gutsche, Gunnar; Ziegler, Andreas
ABSTRACT: Based on data from a representative survey among citizens in Germany during the first peak of the COVID-19 crisis, this paper empirically examines the acceptance of climate-oriented economic stimulus programmes and several further individual climate policy measures. On the basis of our descriptive analysis, we find no evidence that support for such policy measures in Germany is very different during the COVID-19 crisis, compared to before the crisis. However, our econometric analysis points to the relevance of economic concerns. For example, a perceived deterioration of the general economic situation due to the COVID-19 crisis (and thus sociotropic concerns) has a significantly negative effect on the acceptance of climate-oriented economic stimulus programmes. Our econometric analysis also reveals that 'pocketbook' or egotropic concerns are even more relevant since individuals with concerns about their personal economic situation due to the COVID-19 crisis are significantly less supportive of several individual climate policy measures, especially if these lead to higher costs in daily life and are thus directly financially unfavourable. In addition, an identification with socially oriented policy has a significantly positive effect on support for climate policy measures that are financially beneficial for socially underprivileged groups and a significantly negative effect on support for policy measures that are financially unfavourable for them. Our estimation results thus point to the importance of social aspects for the acceptance of climate-oriented policy measures. We also discuss several climate policy implications. For example, our estimation results suggest that individually perceived economic and financial concerns due to the COVID-19 crisis should be addressed and ideally reduced to increase public support of climate-oriented policy measures. Key policy insights: We find no evidence that the acceptance of climate policy measures in Germany is very different during the COVID-19 crisis, compared to before the crisis. Our empirical results are in line with the idea that economic downturns or crises can decrease the acceptance of climate-oriented policy measures among individuals with concerns about their personal economic situation. Our empirical analysis also points to the relevance of social aspects for support for climate policy measures. Therefore, general economic concerns due to the COVID-19 crisis should be addressed and ideally reduced to increase public support for climate-oriented policy measures. In addition, successful climate policy should be socially oriented and should consider distribution effects.